Deciphering highly potent natural abscisic acid agonists for binding to pyrabactin resistance 1 receptor through computational approaches - Pallavi M. Shanthappa; H.G. Gowtham; Poojitha B. Sridhara Setty; Saleh S. Alhewairini; Jayanthi Barasarathi; Pallavi Singh; M. Murali; Riyaz Sayyed; Shiva Prasad Kollur (Scientific Reports)
Abstract Abscisic acid (ABA) agonists bind to the same receptors as ABA in plant cells and exhibit similar physiological effects. Even though synthetic ABA agonists like Pyrabactin, Quinabactin, Cyanabactin, and Opabactin can bind to the PYR1 receptor, no plant-derived natural ABA agonists have been reported. The present study explored the highly potent natural ABA agonists through the target inhibition efficacy of phytochemicals from the different parts of the Ficus carica plant against the binding of pyrabactin resistance 1 (PYR1) receptor (PDB: 3K3K) using computational approaches. Molecular docking analysis confirmed that among the 99 phytochemicals, five phytochemicals, such as Chlorogenic acid, Rutin, Quercetin, Schaftoside, and Imperatorin, were potentially bound at the active binding site of the PYR1 receptor target with the best docking scores below − 8.0 kcal/mol compared to other compounds and positive control ABA. Further, the ABA showed a − 7.6 kcal/mol docking score against the PYR1 receptor. Based on the best docking scores, out of 99 phytochemicals, five lead phytochemicals (viz., Chlorogenic acid, Rutin, Quercetin, Schaftoside and Imperatorin) and positive control (ABA) were further subjected to molecular dynamics (MD) simulation, principal component analysis (PCA), free energy landscape (FEL)and Molecular Mechanics/Poisson-Boltzmann Surface Area (MM/PBSA) analysis. The results have proved that Rutin and Schaftoside were found to form the energetically stable complex with the PYR1 receptor at both 300 K and 325 K. Moreover, the result of the MM/PBSA technique indicated that Rutin and Schaftoside bound PYR1 receptor complexes exhibited lower binding free energy compared to ABA at both 300 K and 325 K. Considering all the results, the study concluded that Rutin and Schaftoside phytochemicals can be highly potent natural ABA agonists with considerable efficacy in binding to the PYR1 receptor active site. The study further needs the experimental validation of these phytochemicals (such as Rutin and Schaftoside) to understand their PYR1 receptor binding potential and for their use in sustainable agriculture.